Bacterial targets of fecal host miRNAs in high-fat diet-fed mice - Laila Silamiķele; Ivars Silamiķelis; Patrīcija Paulīne Kotoviča; Jānis Kloviņš (PLoS ONE, 2025)
The gut microbiome composition is intricately linked to the host’s health status, yet the mechanisms underlying its interaction with the host are not fully understood. MicroRNAs (miRNAs), facilitating intercellular communication, are found in bodily fluids, including the intestinal content, where they may affect the microbiome. However, their role in type 2 diabetes (T2D)-associated microbiome and treatment implications are not explored. Our study investigated how host miRNAs may influence gut microbiome changes related to metformin treatment in a T2D mouse model. Analyzing fecal and gut mucosal samples via small RNA sequencing, we correlated results with microbiome sequencing data, identifying miRNA-microbiome correlations, bacterial targets, and proteins targeted in these bacteria. Significant differences in miRNA expression based on diet and intestinal location were noted, with minor effects from metformin treatment in the proximal small intestine of non-diabetic male mice. Key fecal miRNAs targeting bacteria included mmu-miR-5119, mmu-miR-5126, mmu-miR-6538, and mmu-miR-2137, primarily affecting Oscillospiraceae_NOV, Lachnospiraceae_NOV, and Bacteroides. Our analysis of targeted proteins revealed diverse biological and molecular effects. Further research into miRNA-bacteria interactions could lead to new strategies for manipulating the gut microbiome in T2D and beyond.